Chemoport-related right innominate vein stenosis in patients with colorectal cancer: A retrospective risk factor analysis - Junghoon Kim; Jeong Sub Lee; Choong Guen Chee; Jihoon Woo; Youngjune Kim; Eugene Lee; Joon Woo Lee; Sang Il Choi (PLoS ONE, 2026)
Little information is available regarding the factors that contribute to the occurrence of right innominate vein stenosis in patients with chemoports. Thus, the aims of this study were to evaluate the prevalence of chemoport-related right innominate vein stenosis (CR-RIVS) in patients with colorectal cancer and to identify factors associated with increased CR-RIVS risk. This retrospective study included patients with colorectal cancer (age, ≥ 19 years) who underwent their first chemoport insertion via the right internal jugular vein between August 2015 and August 2020. The prevalence of CR-RIVS was evaluated using follow-up contrast-enhanced chest computed tomography post-chemoport insertion. Risk factors were analyzed using Classification and Regression Tree, Kaplan-Meier survival, and Cox regression analyses. A subgroup analysis was also conducted among patients in palliative care to assess the impact of bevacizumab and cetuximab treatment on the prevalence of CR-RIVS. Among 1,442 patients with colorectal cancer (mean age, 62.1 ± 11.8 years; 850 males), the prevalence of CR-RIVS was 6.6%. The median time from chemoport insertion to CR-RIVS occurrence was 405 days (interquartile range, 256–908 days). The Classification and Regression Tree analysis identified palliative settings as the key predictor of CR-RIVS. Age, palliative settings, and a time×palliative setting interaction were identified as statistically significant variables ( p < 0.001). In the 728 palliative patients, bevacizumab treatment was significantly associated with a higher risk of CR-RIVS (hazard ratio = 1.51, 95% confidence interval: 1.25–1.82, P < 0.001), whereas cetuximab was not ( p = 0.85). The CR-RIVS-free probability was lower in patients receiving palliative chemotherapy than in those undergoing adjuvant chemotherapy ( p < 0.001); it was also lower in the bevacizumab-treated patients ( p < 0.001) in the palliative setting subgroup analysis. In summary, the prevalence of CR-RIVS was 6.6% in patients with colorectal cancer. Bevacizumab use showed the strongest association with CR-RIVS occurrence in the palliative subgroup analysis.